2007
DOI: 10.12671/jkfs.2007.20.3.260
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of New Compression Fractures in Adjacent Vertebrae after Percutaneous Vertebroplasty

Abstract: Jo u rn a l o f th e K o re a n F ra ctru re S o cie ty V o l. 2 0 , N o . 3 , Ju ly , 2 0 0 7 260 통신저자:민 상 혁Tel:041-550-3953․Fax:041-550-3950 E-mail:osmin71@naver.comAddress reprint requests to:Sang-Hyuk Min, M.D. Materials and Methods:The study was conducted on 46 patients in whom 296 patients were performed during last 9 years. We were especially concerned with the restoration rate of vertebral height and kyphotic angle and estimated them on simple X-ray films. Results: In patients experienced subsequent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 19 publications
3
41
0
2
Order By: Relevance
“…In addition, the stiffening effect of the cement in the infiltrated VB may create an adverse load distribution that has the potential to create an accelerated rate of adjacent vertebral failure, similar to those observed in augmentation of osteoporotic VCF. 24,44,45 It is possible to see the development of lesionspecific bone cements with distinct properties for achiev- ing the appropriate delivery and the desired mechanical integrity for the different patterns of infiltration. This may include specific cement augmentation procedures such as concentrated void filling, for example in bone metastases vertebrae, or a more diffuse support within an MM scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the stiffening effect of the cement in the infiltrated VB may create an adverse load distribution that has the potential to create an accelerated rate of adjacent vertebral failure, similar to those observed in augmentation of osteoporotic VCF. 24,44,45 It is possible to see the development of lesionspecific bone cements with distinct properties for achiev- ing the appropriate delivery and the desired mechanical integrity for the different patterns of infiltration. This may include specific cement augmentation procedures such as concentrated void filling, for example in bone metastases vertebrae, or a more diffuse support within an MM scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the greatest challenge may arise from complications similar to those observed in osteoporotic VCFs, in which there is an accelerated rate of adjacent VB fracture following PVP. 24,28,44,45 Here the relatively rapid degradation of bone associated with some malignances may lead to a higher than anticipated incidence of these additional skeletal system-related events.…”
mentioning
confidence: 99%
“…It has been reported that adjacent vertebrae are the most common site of subsequent fractures after cement augmentation procedures including vertebroplasty and kyphoplasty, which uses balloons to create cavities before cement injection (incidence, 41%-76%). [5][6][7][8][9][10]26,27 From preoperative clinical or radiologic datasets, previous studies have proposed risk factors related to adjacent fractures including low body mass index, 9,11 location of thoracolumbar junction, 12 the presence of cleft, 6,13 and shorter distance from the treated vertebrae. 12 In addition, Lee et al 5 reported that advanced age of the patient, treatment of multiple vertebrae, and severe wedge deformity were risk factors for subsequent fractures.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 We identified small size of vertebrae before treatment as a risk factor for subsequent fractures, seen in 12% of vertebrae adjacent to the treated vertebral bodies, probably reflecting the severity of collapsed vertebrae as an indicator for new fracture. On the basis of the postoperative images, the presence of intradiskal leak 9,14,15 and greater height restoration 12 were also considered to be potential risk factors. In this study, we used only preoperative MDCT for evaluation because our intention was to make a good patient selection preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been some reports on further compression of previously treated vertebrae 22,29,30,34,36 and newly developed fractures in adjacent vertebrae 12,13,19,24,28,33,38,46,49 after PVP or PKP with no additional trauma. Heo et al 22 found recollapse of the same vertebra treated with PVP.…”
mentioning
confidence: 99%